CT scan Imaging – A Modality of Choice in Patients Having Head Injury - Aruna Ramchandra Pawar; Suhas Dadarao Alone (International Journal of Medical Research and Review, 2015)
Introduction: Today in world of growing population and increase vehicle use, trauma is the leading cause of death in children, young and adults. Head injury is the major contributor to mortality in over half of these cases. Neuroimaging is fundamental for diagnosis and management of patients with head injury. In this new era of development computed tomography has become the primary modality of choice. The main objective of this study is to assess the utility and importance of CT scan imaging in head injury patients.Methods: This is retrospective study of one year. Out of 120 patients males were 96 and females were 24 in number.Results: Male predominance is seen in this study. Patients up to the age of 70 years were considered. 6 cases were found up to the age of 15 years. 99 cases were found of age of 16 years to 40 years. 15 cases were found above the age of 40 years. Out of 120 cases 80 patients suffered from skull fractures. Most common lesion indentified in CT was brain contusion in 42 patients followed by epidural collection in 9 cases, subdural haematoma in 19 cases, Intracerebral haematoma in 15 cases, localised brain edema in 23 cases, diffuse brain edema 10 cases and pneumocephalus 2 cases were observed.Conclusion: CT scan imaging is a prime important tool in the diagnosis of various pathological abnormalities in the patients suffering from head injury which is important for planning the initial life saving treatment.